INSAN KAMIL DALAM TASAWUF IBNU ARABI SEBAGAI PARADIGMA FILSAFAT PENDIDIKAN ISLAM - Ibnu Ali (Dewan Pendidikan Pamekasan, 2022)
Education as internalization and socialization media is still considered as unsuccessful for humanizing human during this period. The indication is the fenomenon of dehumanization indicated by the emergence of a number of social and humanitarian problems such as moral decadence,crime, and others that were often commetted by educated people. So based and this case, the education system has a lot of approacshes to touch many aspect considered the most effective in achieving educational goals. But many of them are still using an approach oriented on the intellectual capabilities that neglect other aspect that is more important. This research study is to look for other aspects that rely on more important. Namely through the paradigm of Ibnu Arabia boat perpect man (insan kami) which he found conclusion that man has an ontological and epistemological structure which the source is Qolb (heart/soul) as the central attitudes and human will. Thus it can be concluded that education of Sufism may be the most effective approach in achieving educational goals.